Market incentives for system-friendly designs of wind turbines - Nils May; Karsten Neuhoff; Frieder Borggrefe (DIW Economic Bulletin, 2015)
Up until now, wind turbines have been designed to generate electricity at the lowest possible total cost, independent of this electricity's market value. With an increasing penetration of wind power in the system, the market value of electricity generated by wind turbines is declining, since wind turbines tend to produce electricity at the same time. For this reason, it will be important in the future to design wind turbines in a system-friendly manner so that a larger proportion of electricity generation occurs in hours with lower wind speeds. This can be achieved with higher towers, longer rotor blades, and generators with comparatively low power ratings. According to model calculations, a fixed feed-in tariff provides insufficient incentives for such plant designs, which would be especially system-friendly in the context of further expansion of renewable energies. Likewise, direct marketing with a floating market premium does not provide adequate incentives if investors take the current electricity prices as a basis for their planning and project financing. By contrast, in a new instrument that is being proposed here-the so-called "production value-based benchmark approach"-the level of the feed-in tariff is based on the expected future market value of the wind turbine's electricity. In this way, incentives for investments in plants that will be especially system-friendly in the future could already be created in the present. At the same time, questions regarding the actual design and the practical implementation still need to be resolved.
Keywords: Q42; Q55; O38; 330; feed-in tariff; wind turbine technology; wind power investments